The Effect of Financial Ratios, Corporate Governance, and Macroeconomics on Financial Distress in Tourism Industry Service Companies Listed on the Indonesia Stock Exchange - Mulia Putri, Cika; Tasman, Abel (Financial Management Studies, 2023)
This study aims to analyze the effect of (1) profitability on financial distress, (2) liquidity on financial distress, (3) leverage on financial distress, (4) gender diversity on financial distress, (5) institutional ownership on financial distress, (6) ) inflation on financial distress, (7) interest rates on the financial distress of tourism industry service companies listed on the Indonesia Stock Exchange before and during the Covid-19 Pandemic. While the sample in this study was determined using the purposive sampling method, namely tourism industry service companies with data prior to the Covid-19 Pandemic for six consecutive years from 2014-2019 so that a total sample of 18 companies was obtained with 108 observational data and data during the Covid Pandemic. -19 for two consecutive years from 2020-2021 so that a total sample of 18 companies was obtained with 144 observational data. The analytical method used is the logistic regression method using the IBM SPSS Statistics 25 program. The results of this study concluded before the Covid-19 Pandemic that (1) profitability as measured by ROE had a significant negative effect on financial distress, (2) liquidity as measured by CR was negative and did not have a significant effect on financial distress, (3) leverage as measured with DER having a significant negative effect on financial distress, (4) gender diversity is negative and has no significant effect on financial distress, (5) institutional ownership is positive and has no significant effect on financial distress, (6) inflation is negative and has no significant effect on financial distress, (7) positive interest rates and no significant effect on financial distress. While the results of research during the Covid-19 Pandemic concluded that (1) profitability as measured by ROE had a significant negative effect on financial distress, (2) liquidity as measured by CR had a significant negative effect on financial distress, (3) leverage as measured by DER negative and has no significant effect on financial distress, (4) gender diversity has a positive and no significant effect on financial distress, (5) institutional ownership has a significant positive effect on financial distress, (6) inflation has a significant negative effect on financial distress, (7) ethnicity positive interest and no significant effect on financial distress.